Introduction to the Logical Investigations - Husserl, Edmund. author. aut Link
XXX, 62 p.
Keywords: TO THE LOGICAL INVESTIGATIONS A DRAFT OF A PREFACE TO THE LOGICAL INVESTIGATIONS ( 1913) Edited by EUGEN FINK Translated with Introductions by PHILIP J. BOSSERT and CURTIS H. PETERS • MARTINUS NIJHOFF THE HAGUE 1975 © I975 by Martinus Nijhoff. The Hague. Netherlands All rights reserved. including the right to translate or to reproduce this book or parts thereof in any form ISBN-I3: 978-90-247-1711-8 e-ISBN-I3: 978-94-010-1655-1 DOl: 10. 1007/978-94-010-1655-1 TO HERBERT SPIEGELBERG ESTEEMED SCHOLAR, MENTOR, FRIEND ACKNOWLEDGEMENTS We would like to express our thanks to H. L. Van Breda, director of the Husserl-Archiv (Louvain), for his approval and encouragement of this project, and to Professor Dr. Gerhart Husserl, Professor Dr. Eugen Fink and the editors of Tijdschrift voor Philosophie for their permission to undertake it. We also owe a debt of appreciation to Dr. Karl Schuhmann of the Catholic University of Louvain and to Dr. Elmar Holenstein, Dr. Edi Marbach and Mr. Rudolf Bernet of the Husserl-Archiv (Louvain) for their help in reading the original manuscripts and for putting their excellent knowledge of the Husserl "Nachlass" preserved at the Archives at our disposal. We especially wish to thank Professor Herbert Spiegelberg whose careful and critical reading of our manuscript at an earlier stage resulted in numerous suggestions for its improvement; and, last but not least, our wives, Jane and Pam, for their help in preparing the typescripts. TABLE OF CONTENTS Translator's Introductions XI I. HISTORICAL INTRODUCTION XI II. THEMATIC INTRODUCTION XX III.